Physical growth in children with transfusion-dependent thalassemia - Harish K Pemde; Jagdish Chandra; Divya Gupta; et al (Dove Medical Press, 2011)
Harish K Pemde, Jagdish Chandra, Divya Gupta, Varinder Singh, Rajni Sharma, AK DuttaDepartment of Pediatrics, Lady Hardinge Medical College, Kalawati Saran Children's Hospital, New Delhi, IndiaObjective: To describe physical growth and related factors in transfusion-dependent thalassemia patients.Methods: This is a cross-sectional analysis of the records of the patients registered at and being followed up by the Thalassemia Day Care Center (TDCC) at Kalawati Saran Children's Hospital, New Delhi, India. Clinical and laboratory parameters were recorded on a spreadsheet for analysis. Clinical parameters included weight, height, sexual maturity ratings, and general and systemic physical examination. Laboratory parameters included pretransfusion hemoglobin (Hb), periodic serum ferritin, and tests for viral markers of human immunodeficiency virus (HIV) and hepatitis B and C. Z-scores for weight, height, and body mass index (BMI) were calculated using World Health Organization reference data. Statistical analysis was carried out using Microsoft Excel® and Stata® software.Results: Out of 214 patients registered at the TDCC since 2001, 154 were included in this study. The mean age of patients was 9.19 years (range 0.5–20 years). Pretransfusion Hb was well maintained (mean 9.21 g/dL; 95% confidence interval [CI]: 9.06–9.36), but the mean serum ferritin levels were approximately three times (3112 ng/mL) the desired value despite the patients being on deferiprone (72%) or deferasirox (25%). One-third (33.11%) of the patients had short stature, 13% were thin, and 10.82% were very thin (BMI z-score <-3). No patient was overweight or obese. Linear regression coefficient showed that for every 1-year increase in age, the mean ferritin value increased by 186.21 pg/mL (95% CI: 143.31–228.27). Height z-scores had significant correlation with mean ferritin levels, whereas correlation with mean pretransfusion Hb was not significant statistically. Mean ferritin levels were significantly higher in patients with short stature than in the patients with normal height. Regression analysis showed that an increase of 3571 units of serum ferritin was associated with a decrease of one point in height z-scores. One-fifth (19.40%) of adolescent patients had delayed puberty.Conclusion: Approximately one-third (33.11%) of patients with transfusion-dependent thalassemia major were of short stature. In this group of patients with pretransfusion Hb levels maintained at desired levels, physical growth was correlated with status of iron overload.Keywords: thalassemia, growth, body mass index, serum ferritin